THE INFLUENCE OF JOB TRAINING AND DEVELOPMENT HUMAN RESOURCES (HR) ON PERFORMANCE EMPLOYEES IN THE DISASTER MANAGEMENT AGENCY NORTH LABUHAN BATU REGENCY AREA - Sapta Surya Lesmana; Sri Gustina Pane; Nur Augus Fahmi (CV. RADJA PUBLIKA, 2025)
This study aims to determine whether job training and human resource development (HRD) have an impact on employee performance at the Regional Disaster Management Agency (BPBD) of North Labuhan Batu Regency. This study uses primary data by distributing questionnaires to all employees. The sampling technique uses the SPSS program. The population used is 66 respondents where the entire population is sampled. The techniques used in this study use data quality tests, classical assumption tests, multiple linear analysis tests and hypothesis tests. The results obtained are job training has a positive and significant effect on employee performance at the Regional Disaster Management Agency (BPBD) of North Labuhan Batu Regency and Human resource development (HRD) has a positive and significant effect on employee performance at the Regional Disaster Management Agency (BPBD) of North Labuhan Batu Regency, as well as job training and human resource development (HRD) simultaneously have a positive and significant effect on employee performance at the Regional Disaster Management Agency (BPBD) of North Labuhan Batu Regency.